Development of a Novel Avian Vaccine Vector Derived From the Emerging Fowl Adenovirus 4 - Pan, Qing; Zhang, Yu; Liu, Aijing; Cui, Hongyu; Gao, Yulong; Qi, Xiaole; Liu, Changjun; Zhang, Yanping; Li, Kai; Gao, Li; Wang, Xiaomei (Frontiers in Microbiology, 2021)
Severe hepatitis-hydropericardium syndrome (HHS) associated with a novel viral genotype, fowl adenovirus 4 (FAdV-4), has emerged and is widely spread in China since 2015, causing severe economic losses to the poultry industry. We previously reported that the hexon gene is responsible for pathogenicity and obtained a non-pathogenic hexon-replacement rHN20 strain; however, the lack of information about the non-essential regions for virus replication limits the development of a FAdV-4 vector. In this study, we first established an enhanced green fluorescent protein (EGFP)-indicator virus based on the FAdV-4 reverse genetic technique, which is effective for batch operations in the virus genome. On this foundation, ten open reading frames (ORFs) at the left end and 13 ORFs at the right end of the novel FAdV-4 genome were separately deleted and identified as non-essential genes for virus replication, providing preliminary insertion sites for foreign genes. To further improve the feasibility of use as a vaccine vector, seven combinations of ORFs were successfully replaced with EGFP without affecting the immunogenicity of the vector backbone. Finally, a recombinant rHN20-vvIBDV-VP2 strain, expressing the VP2 protein of very virulent infectious bursa disease virus (vvIBDV), was rescued and showed complete protection against FAdV-4 and vvIBDV. Thus, the novel FAdV-4 vector could provide sufficient protection for HHS and efficient delivery of the exogenous gene. Overall, our findings systemically identified 23 non-essential ORFs for FAdV-4 replication and seven foreign gene insertion regions, providing valuable information for an in-depth understanding of the novel FAdV-4 pathogenesis and development of multivalent vaccines.